Combined Effects of Dual-Scale Modified Surface with Micro- and Nanostructures on the Cellular Biocompatibility, Osteoinduction, and Antibacterial Properties of Titanium Implants - Shaheer Maher; Nenad L. Ignjatović; Miloš Lazarević; Sanja Petrović; Andrijana Žekić; Dusan Losic (Journal of Functional Biomaterials)
Titanium implants are widely used in biomedical applications due to their excellent mechanical properties and biocompatibility. However, implant-associated bacterial infections and suboptimal osseointegration remain significant challenges. Recent studies have demonstrated that the interplay between micro- and nanostructures can enhance both biocompatibility and antibacterial properties. This study explores the synergistic effects of hierarchical and dual surface topography on Ti surfaces with micro- and nanostructures to demonstrate their ability to promote cellular biocompatibility and osteoinduction while simultaneously inhibiting bacterial colonization. The combination of selective laser melting (SLM) to create micro-structured surfaces and hydrothermal processes is used to generate distinctive nanopillar structures. By integrating nanoscale features that mimic the extracellular matrix with microscale topographies that influence cellular responses, we achieve a balance between enhanced osseointegration and antimicrobial performance. The physicochemical properties of these dual-scale topographies are characterized through cellular assays using dental pulp stem cells (DPSCs), demonstrating sustained support for long-term cell viability (above 78% in MTT and NR assays (p < 0.05), low levels of LDH release, and high levels of cellular migration) and osteoinduction (statistically significant (p < 0.0001) ALP activity increase and higher levels of calcified matrix deposition, upregulation of ALP and OCN genes compared with smooth surface topographies). Their antibacterial properties against S. aureus and E. coli showed a significant reduction (p < 0.05) in bacterial attachment and biofilm formation. Our findings highlight the potential of multi-scale surface modifications as a promising strategy for next-generation titanium implants, paving the way for improved clinical outcomes in orthopedic and dental applications.